Avaliação do uso de múltiplas linhas para a determinação de metais por espectrometria de emissão óptica com plasma acoplado indutivamente - Schiavo, Daniela (Universidade Federal de São Carlos, 2010)
The aim of this thesis was the evaluation of the use of multiple lines for determination of metals by inductively coupled plasma optical emission spectrometry (ICP OES) with Littrow optical system, Echelle polychromator and CCD solid-state detector. This instrument arrangement allows fast simultaneous measurements of several spectral lines. The combination of more than two emission lines for each element led to advantages as the minimization of systematic errors caused by spectral interferences and matrix effects, improvement of the figures of merit such as limits of detection (LOD) and quantification (LOQ), and better accuracy for determination of metals in water samples. In this work, several spectral lines were combined for the determination of Al, Cd, Co, Cr, Mn, Pb, U and Zn and different operating conditions were evaluated. Afterwards, parameters for evaluation of the calibration model were calculated to select which combination of emission lines provided the best accuracy (lowest values of PRESS Predicted error sum of squares and RMSEP Root means square error of prediction). A total of 63 different combinations of emission lines were evaluated for each element. Lower limits of detection (LOD) were obtained with multiple lines, i. e., 7.1, 0.5, 6.9, 0.042, 12.9, 28.1 and 6.7 μg L-1 (n = 10) for Al, Cd, Co, Cr, Mn, Pb and Zn, respectively, in the presence of concomitants. The LODs obtained for the most intense emission line were 15.9, 0.7, 8.4, 0.074, 22.5, 26.2 and 9.6 μg L-1(n = 10) for these same sequence of elements in the presence of concomitants. The evaluation of the accuracy of the developed procedure was demonstrated using one water certified reference material (Lot#005914 High-Purity Standards), Tomato Leaves (NIST 1573a) and Bovine Muscle (NIST 8414). Based on the figures of merit it can be concluded that the use of multiple lines improved the sensitivity making feasible the determination of analytes according to the target values required for the current environmental legislation for water samples (CONAMA resolution no 357) and this approach can also be employed as a tool to verify the accuracy of an analytical procedure using ICP OES. However, the selection of the emission lines is critically dependent on the matrix complexity and consequently on the resulting spectral environment, and these effects were more pronounced when working with digests of plant and animal tissues.
Evaluation of the use of multiple lines for determination of metals by inductively coupled plasma optical emission spectrometry
Keywords: ICP-OES; Metais; Somatória; CIENCIAS EXATAS E DA TERRA::QUIMICA